Tissue-specific control of galectin-1-driven circuits during inflammatory responses - Cutine, Anabela María (2021)
The relevance of glycan-binding proteins in immune tolerance and inflammation has been well established, mainly by studies of C-type lectins, siglecs and galectins, both in experimental models and patient samples. Galectins, a family of evolutionarily conserved lectins, are characterized by sequence homology in the carbohydrate-recognition domain, atypical secretion via an endoplasmic reticulum-Golgi-independent pathway and by the ability to recognize β-galactoside-containing saccharides. Galectin-1 (Gal-1), a prototype member of this family, displays mainly anti-inflammatory and immunosuppressive activities, although, similar to many cytokines and growth factors, it may also trigger paradoxical pro-inflammatory effects under certain circumstances. These dual effects could be associated to tissue-, time- or context-dependent regulation of galectin expression and function, including particular pathophysiologic settings and/or environmental conditions influencing the structure of this lectin, as well as the availability of glycosylated ligands in immune cells during the course of inflammatory responses. Here, we discuss the tissue-specific role of Gal-1 as a master regulator of inflammatory responses across different pathophysiologic settings, highlighting its potential role as a therapeutic target. Further studies designed at analyzing the intrinsic and extrinsic pathways that control Gal-1 expression and function in different tissue microenvironments may contribute to delineate tailored therapeutic strategies aimed at positively or negatively modulating this glycan-binding protein in pathologic inflammatory conditions.